Utilising adaptive real-time control in removing organic chemicals in stormwater biofilters - Jiadong Zhang; Veljko Prodanovic; Denis M. O’Carroll; David T. McCarthy; Kefeng Zhang (Water Research, 2026)

Using surrogates to predict trace organic contaminant removal in stormwater biofilters - Jiadong Zhang; Veljko Prodanovic; Denis M. O’Carroll; Kefeng Zhang (Water Research, 2026)

Cost-effective urban farming with alternative water sources treated by nature-based solutions: A critical review of global practices - Niloofar Shoja Razavi; Kefeng Zhang; Veljko Prodanovic (Agricultural Systems, 2026)

Nitrogen removal from high-ammonia wastewater using vegetated biofiltration systems: Insights from 18-month mesocosm study - Veljko Prodanovic; Lihao Yuan; Ana Deletic; Kefeng Zhang (Bioresource Technology, 2026)

Urban greening and water strategies are key to adapt Australian cities to climate change and urban growth - Valentina Marchionni; Christopher Szota; Claire Farrell; Stephen J. Livesley; Kerry A. Nice; Veljko Prodanovic; Sally Thompson; Pui Kwan Cheung; Hamideh Nouri; Mathew Lipson; Brandon Winfrey (Journal of Hydrology, 2026)

Anammox in nature-based systems for urban water management: A review and Bayesian assessment of environmental drivers - Yinghui Tang; Veljko Prodanovic; Denis M. O'Carroll; Min Zheng; Kefeng Zhang (Journal of Environmental Management, 2025)

Fate of wastewater trace organic chemicals in vegetated biofiltration systems - Kefeng Zhang; Lihao Yuan; Ana Deletic; Veljko Prodanovic (Water Research, 2025)

Long-term performance of eight green wall plants in removing xenobiotic organic compounds from greywater across varied operational conditions - Hafiz M. Abd-ur-Rehman; Kefeng Zhang; Ana Deletic; Stuart J. Khan; Veljko Prodanovic (Journal of Water Process Engineering, 2025)

Real time control of stormwater biofilters improves the removal of organic chemicals - Jiadong Zhang; Veljko Prodanovic; Denis M. O'Carroll; Zhaozhi Zheng; Kefeng Zhang (Water Research, 2024)

Urban nature-based solutions planning for biodiversity outcomes: human, ecological, and artificial intelligence perspectives - Veljko Prodanovic; Peter M. Bach; Milan Stojkovic (Urban Ecosystems, 2024)
Nature-based solutions (NBS) harness ecosystem services for urban enhancement, promoting biodiversity, habitat creation, and water management while improving human well-being. However, decision-making often favours specific NBS designs, leading to uneven benefits distribution. Whereas human-centric NBS design relies on convenience, financial sustainability, historical aspects, and amenity increase through NBS technical solutions, flora- and fauna-centric (or eco-centric) design targets spatial connectedness of blue-green spaces, increase in species richness, and habitat within urban centres. Both approaches can shape the urban biodiversity landscape, yet; they often clash around planning priorities. Recent advances in AI offer potential for AI-centric urban planning, though its role remains unclear. This study examines the interplay between biodiversity and NBS planning across human-, eco-, and AI-centric domains, aiming for balanced urban outcomes. We blended narrative, integrative, and systematic literature review and propose future steps for more balanced NBS development. The findings of this work suggest that AI presents an opportunity for a more balanced NBS design through its applications in climate change prediction, water management, and project visualisation. Incorporating AI into urban planning tools can expedite modelling process, improve stakeholder communication, and enhance project outcomes visualisation. By integrating human, eco, and AI-centric approaches, urban planners can foster resilience and sustainability in NBS implementation, ensuring equitable distribution of benefits across urban landscapes.

Impact of electrochemically generated iron on the performance of an anaerobic wastewater treatment process - Zhetai Hu; Shihu Hu; Pei-Ying Hong; Xueqin Zhang; Veljko Prodanovic; Kefeng Zhang; Liu Ye; Ana Deletic; Zhiguo Yuan; Min Zheng (Science of The Total Environment, 2023)

Nitrification potential of daily-watered biofiltration designs for high ammonium wastewater treatment - Veljko Prodanovic; Kefeng Zhang; Min Zheng; Shihu Hu; Pei-Ying Hong; Zhiguo Yuan; Ana Deletic (Science of The Total Environment, 2023)